Tinjauan Fikih Awlawiyah Terhadap Praktik Penyaluran Zakat Pada Baznas Provinsi Kalimantan Selatan - Hakim, Budi Rahmat; Wafi, Akhmad; Wijaya, Almejiem Aditya; Fitriani, Nida; Ridani, Muhammad Noor (PT. Sharia Journal and Education Center, 2024)
Abstract Baznas is a non-governmental organization that is tasked with collecting and distributing zakat to those who are entitled to receive it. In order to maximize the impact of zakat distribution, Baznas makes programs that are divided into several distribution targets consisting of humanitarian programs, syiar and advocacy, education, and health. Of these programs, the humanitarian program receives the most funding, followed by syiar and advocacy, then education and health. In Islam, there is the concept of fiqh awlawiyat or fiqh of priorities. Priority jurisprudence discusses the procedure for choosing priorities between several benefits that require one to take precedence. Seeing in the distribution of zakat by Baznas there is a priority scale, it is interesting to examine it from the perspective of fikih awlawiyat. This research uses normative legal research method with fikih awlawiyat paradigm as the analysis knife. The purpose of this study is to determine the suitability of the priority scale in the distribution of zakat by Baznas with the theory of fikih awlawiyat. In the end, the conclusion of this research found the suitability between the priority scale of zakat distribution by Baznas with the theory of fikih awlawiyat. Keywords: zakat, baznas, awlawiyah fiqh Abstrak Baznas merupakan lembaga non pemerintah yang bertugas untuk mengumpulkan dan menyalurkan zakat kepada para pihak yang berhak menerimanya. Demi memaksimalkan dampak penyaluran zakat, maka Baznas membuat program-program yang terbagi pada beberapa target pendistribusian yang terdiri dari program kemanusiaan, syiar dan advokasi, pendidikan, dan kesehatan. Dari beberapa program tersebut, program kemanusiaan mendapat kucuran dana yang paling besar, lalu disusul syiar dan advokasi, kemudian pendidikan dan kesehatan. Dalam Islam, terdapat konsep fikih awlawiyat atau fikih prioritas. Fikih prioritas membahas tentang tata cara memilih prioritas antara beberapa kemaslahatan yang menuntut ada yang didahulukan. Melihat dalam penyaluran zakat oleh Baznas terdapat skala prioritas, maka menarik untuk menelaahnya dari sudut pandang fikih awlawiyat. Penelitian ini menggunakan metode penelitian hukum normatif dengan paradigma fikih awlawiyat sebagai pisau analisisnya. Tujuan dari penelitian ini adalah untuk mengetahui kesesuaian skala prioritas pada penyaluran zakat oleh Baznas dengan teori fikih awlawiyat. Pada akhirnya, kesimpulan dari penelitian ini menemukan kesesuaian antara skala prioritas penyaluran zakat oleh Baznas dengan teori fikih awlawiyat. Kata Kunci : Zakat, Baznas, Fikih Awlawiyah